Effect of replacing urea-treated sugarcane bagasse with different proportions of barley on some blood biochemical traits of Arabian sheep - fadhil, alaa; jalal ogali usur (University of Thi-Qar Journal of agricultural research, 2025)
This study aimed to investigate the effect of substituting barley with urea-treated sugarcane bagasse at different ratios (0, 10, 20 and 30%) on blood biochemical parameters in the serum of Arabian lambs. The study included 16 Arabian lambs, purchased from local markets in Basra Governorate, at the age of 5-6 months, with an average weight of 25 ± 0.75 kg. Lambs were divided into four treatments (4 lambs per treatment). The treatments were: T1 the control (0% sugarcane bagasse treated with urea), T2 (10% sugarcane bagasse treated with urea), T3 (20% sugarcane bagasse treated with urea) and T4 (30% sugarcane bagasse treated with urea). The feeding period was 90 days including 14 days of adaptation. The results showed significant differences (P≤0.05) in total protein concentration (g/L) in favor of the treatments fed urea-treated sugarcane bagasse compared to the control treatment throughout the study period. There were significant differences (P≤0.05) in albumin concentration during the second month of the study in the treatments fed urea-treated sugarcane bagasse compared to the control treatment, while the differences were not significant in the first and third months of the study. There were significant differences (P≤0.05) in globulin concentration during the first and second months in favor of the treatments fed urea-treated sugarcane bagasse compared to the control treatment, while the differences were not significant in the third month. There was a significant increase (P≤0.05) in urea concentration (mmol/L) in the treatments fed urea-treated sugarcane bagasse compared to the control treatment. There was a significant increase (P≤0.05) in creatinine concentration (mmol/L) in the treatments fed urea-treated sugarcane bagasse compared to the control treatment. There was a significant increase (P≤0.05) in the concentration of liver enzymes AST and ALT (IU/L) in the treatments fed urea-treated sugarcane bagasse compared to the control treatment, but these levels remained within the normal range. It is concluded that replacing urea-treated sugarcane bagasse in lamb rations has no negative effect on the health status of lambs.